The Features of Fatimid's Historiography in Islamic Historiography Discourse - Ali Babaei Siab; Fatemeh Janahmadi; Sayed Hashem Aghajari (تاریخ نگری و تاریخ نگاری, 2018)
Researchs on the historiography of the Ismâilis has been less successful among scholars in this field due to the loss of a significant amount of their works. By examining the few remaining works of Ismaili historians and recreating a general image of their lost works based on other sources, research into the historiography of this cult is to some extent possible. The importance of this research is due to the fact that the historiography of the Ismailis has been investigated from the perspective of the followers of this sect in a historical record largely ignored by researchers from this field. In this research, it will be shown what features of the Fatimid historiography in the dominant discourse of Islamic historiography. It seems that the Fatimid historiography, in spite of the advent in the dominant discourse of Islamic historiography and being effected by it, seems to be partly due to features such as the apparent intersection of the theology with the history and the placement of the Ismaili Imam in the center of events, which suggests an attempt for a kind of sacred historiography. It distinguishes itself from the tradition of Islamic historiography and separates it from it. This research has been accomplished through qualitative content analysis and based on library and digital resources.